Increasing prevalence of mental disorders in smokers seeking treatment of tobacco dependence: a retrospective observational study - Zvolska, Kamila; Tichopad, Ales; Stepankova, Lenka; Pankova, Alexandra; Adamcekova, Zuzana; Donin, Gleb; Rafl, Jakub; Kralikova, Eva (BMC psychiatry, 2023)
BACKGROUND: There has been a noticeable relative increase in psychiatric comorbidities among smokers as opposed to the general population. This is likely due to comparatively slower decrease in smoking prevalence among individuals with mental health conditions. This study aims to assess the prevalence trend of past or current mental health disorders in individuals seeking specialized smoking cessation assistance. METHODS: We conducted a retrospective single-centre observational study to assess the presence of mental disorders such as anxiety, depression, bipolar affective disorder, or schizophrenia in personal history of 6,546 smokers who sought treatment at the Centre for Treatment of Tobacco Dependence in Prague, Czech Republic between 2006 and 2019. The study examined the impact of gender, age, and the effect of successive years on the prevalence of the mental disorders using Poisson distribution regression. RESULTS: In the studied cohort, 1,743 patients (26.6%) reported having one or more mental disorders. Compared to patients without a psychiatric disorder, they exhibited similar levels of carbon monoxide in expired air (mean 17 ppm, SD 11 ppm) and scored one point higher on the Fagerström Test of Cigarette Dependence. Among smokers with a mental disorder, women were more prevalent (62%) than men (38%). The prevalence of mental disorders increased on average by 4% every year, rising from 23% in 2006 to 35% in 2019. CONCLUSIONS: Consistent with the observation that the prevalence of smoking among people with any mental disorder is higher and declining at a slower rate than in the general population, there is a steadily increasing percentage of these patients seeking specialized treatment over time. Professionals who offer tobacco dependence treatment should be aware of the upward trend in psychiatric disorders among smokers, as more intensive treatment may be needed. Similarly, psychiatric care should pay attention to smoking of their patients.
Keywords: Humans; Smokers; kuřáci; Psychiatric disorders; prevalence; poruchy vyvolané užíváním tabáku; Female; lidé; Smoking cessation; duševní poruchy; ženské pohlaví; Tobacco Use Disorder; Male; Comorbidity; Retrospective Studies; Mental Disorders; Prevalence; retrospektivní studie; Tobacco dependence; mužské pohlaví; Treatment